2017
DOI: 10.1016/j.jmaa.2016.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Decompositions of preduals of JBW and JBW⁎ algebras

Abstract: Abstract. We prove that the predual of any JBW * -algebra is a complex 1-Plichko space and the predual of any JBW-algebra is a real 1-Plichko space. I.e., any such space has a countably 1-norming Markushevich basis, or, equivalently, a commutative 1-projectional skeleton. This extends recent results of the authors who proved the same for preduals of von Neumann algebras and their self-adjoint parts. However, the more general setting of Jordan algebras turned to be much more complicated. We use in the proof a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Our main result reads as follows. The approach in this paper resembles more the one of [4] than the one of [5]. One reason for this has already been mentioned, in the present paper the proofs and arguments do not make use of the set theoretic tool of submodels.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our main result reads as follows. The approach in this paper resembles more the one of [4] than the one of [5]. One reason for this has already been mentioned, in the present paper the proofs and arguments do not make use of the set theoretic tool of submodels.…”
Section: Introductionmentioning
confidence: 94%
“…A generalization to JBW * -algebras appeared to be non-trivial. In [5] the same authors showed that the predual of any JBW * -algebra is 1-Plichko. The proof was quite different from that given in the setting of von Neumann algebras.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, for example C(K) is 1‐Plichko for any compact space K (see, for example, [, Example 4.10(a)] or [, Theorem 5.5]), but not every C(K) space is Asplund. More generally, dual to any C‐algebra is 1‐Plichko by [, Corollary 1.3] (for further generalizations see ). (2) Let X be an Asplund space.…”
Section: Examples Of Spaces With a Noncommutative Projectional Skeletonmentioning
confidence: 99%
“…Several equivalences from this theorem are already known. The equivalence (1), (5), and (7) is contained in [16,Theorem 8.3.3 and the following remark]. The equivalence (1)⇔(3) is proved in [13,Theorem 15].…”
Section: Duals Of Asplund Spacesmentioning
confidence: 99%